Advances in Magnesium Thixomolding - Lohmüller, Andreas; Scharrer, Martin; Jenning, Ralf; Rauber, Christian; Loos, Michael; Kömpel, Natalie; Hilbinger, Rolf Michael; Hartmann, Mark; Singer, Robert (15th Automotive and User Seminar, 2007)

Comparison of conventional magnesium alloys with Mg-Al-Ca-Zn and Mg-Al-Sr-Zn alloys processed by injection molding - Kömpel, Natalie; Lohmüller, Andreas; Krause, A.; Singer, Robert (8th International Conference on Magnesium Alloys and their Applications, 2009)

Effect of solidification microstructure and Ca additions on creep strength of magnesium alloy AZ91 processed by Thixomolding - Eibisch, Harald; Lohmüller, Andreas; Kömpel, Natalie; Singer, Robert (International Journal of Materials Research, 2008)
The compressive creep behaviour of AZ91 processed by Thixomolding with varying solid phase content (2-45%) was investigated. It can be shown that with increasing solid phase content the creep rate at 150°C is reduced by a factor of 3-10. The results can be rationalised in terms of a grain size effect. The solid phase (primary α-Mg phase solidified prior to mould filling) is relatively coarse (40 um), i. e. the average grain size increases significantly when the material is processed in the semi-solid regime. Grain boundary sliding which is known to contribute significantly to creep deformation depends on the grain size. The creep rate of high pressure die cast material is found to be similar to thixomolded material. The high pressure die cast materials although nominally processed in the fully liquid regime, contains pre-solidified coarse primary α-Mg phase as well. The coarse solid phase particles are formed early in the process when the melt cools rapidly in the shot sleeve. AZ91 with Ca-additions up to 5 wt.% were prepared using a newly developed second feeding system that allows the addition of a second sort of granules to the screw in parallel to the main feed. As expected, Ca increases the creep strength very significantly. The reasons for this increase will be discussed. © Carl Hanser Verlag GmbH & Co. KG.
Keywords: AZ91; Ca addition; Creep resistance; Microstructure; Thixomolding

Mikrostruktur und Warmfestigkeit von Mg-Al- und Mg-Al-Sr-Legierungen bei Verarbeitung im Spritzguss - Kömpel, Natalie (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2013)